Nickel isotope fractionation during laterite Ni ore smelting and refining: Implications for tracing the sources of Ni in smelter-affected soils. (January 2016) - Ratié, G.; Quantin, C.; Jouvin, D.; Calmels, D.; Ettler, V.; Sivry, Y.; Vieira, L. Cruz; Ponzevera, E.; Garnier, J.
Abstract: Nickel isotope ratios were measured in ores, fly ash, slags and FeNi samples from two metallurgical plants located in the Goiás State, Brazil (Barro Alto, Niquelândia). This allowed investigating the mass-dependent fractionation of Ni isotopes during the Ni-laterite ore smelting and refining. Feeding material exhibits a large range of δ 60 Ni values (from 0.02 ± 0.10‰ to 0.20 ± 0.05‰, n = 7), explained by the diversity of Ni-bearing phases, and the average of δ 60 Nifeeding materials was found equal to 0.08 ± 0.08‰ (2SD, n = 7). Both δ 60 Ni values of fly ash (δ 60 Ni = 0.07 ± 0.07‰, n = 10) and final FeNi produced (0.05 ± 0.02‰, n = 2) were not significantly different from the feeding materials ones. These values are consistent with the very high production yield of the factories. However, smelting slags present the heaviest δ 60 Ni values of all the smelter samples, with δ 60 Ni ranging from 0.11 ± 0.05‰ to 0.27 ± 0.05‰ (n = 8). Soils were also collected near and far from the Niquelândia metallurgical plant, to evaluate the potential of Ni isotopes for tracing the natural vs anthropogenic Ni in soils. The Ni isotopic composition of the non-impacted topsoils developed on ultramafic rocks ranges from −0.26 ± 0.09‰ to −0.04 ± 0.05‰ (n = 20). On the contrary, the Ni isotopic composition of the non-ultramafic topsoils, collected close to the plant, exhibit a large variation of δ 60 Ni, ranging from −0.19 ± 0.13‰ up to 0.10 ± 0.05‰ (n = 4). This slight but significant enrichment in heavy isotopes highlights the potential impact of smelting activity in the surrounding area, as well as the potential of Ni isotopes for discerning anthropogenic samples (heavier δ 60 Ni values) from natural ones (lighter δ 60 Ni values). However, given the global range of published δ 60 Ni values (from −1.03 to 2.5‰) and more particularly those associated to natural weathering of ultramafic rocks (from −0.61 to 0.32‰), the use of Ni isotopes for tracing environmental contamination from smelters will remain challenging. Highlights: Smelting and refining Ni ore laterites induce slight Ni isotope fractionation. δ 60 Ni values of anthropogenic Ni product fall within the range of terrestrial samples. Smelting slags are enriched in Ni heavy isotopes with respect to soils samples. Use of Ni isotopes for tracing environmental contamination remains challenging.